Analisis Pengaruh Massa Jenis Kelereng terhadap Nilai Koefisien Restitusi pada Tumbukan Kelereng dengan Lantai menggunakan Smarthphone berbantuan Aplikasi Phypox - Prabowo, Bayu Edy; Lesmono, Albertus Djoko; Handayani, Rif'ati Dina (JURNAL PEMBELAJARAN FISIKA, 2024)
Abstract The research is motivated by the shortcomings in the use of video tracker applications to measure the height of the marble bounce where the camera used to record the marble bounce must have a certain quality so that the video can be analyzed properly by the video tracker application. The purpose of this study is to analyze the effect of the density of marbles on the value of the coefficient of restitution on the collision of marbles with the floor using a smartphone assisted by the Phypox application. This research is an experimental research using graph analysis method. The results showed that marbles with a density of 950 kg/m3 produced a restitution coefficient of 420.1 x 10-3, marbles with a density of 1400 kg/m3 produced a restitution coefficient of 574.4 x 10-3, marbles with a density of 2400 kg/m3 produced a restitution coefficient of 831.7 x 10-3, marbles with a density of 2700 kg/m3 produced a restitution coefficient of 878.1 x 10-3, and marbles with a density of 7600 kg/m3 produced a restitution coefficient of 888.8 x 10-3. Based on the graph analysis, it is concluded that the coefficient of restitution of the impact of the marbles with the floor is getting bigger and closer to the value of 1 if the density of the marbles increases. Keywords : Coefficient of Restitution, Density, Phypox Application